Strength gains and distinct acute blood lactate responses induced by stepwise load reduction training in healthy males - Zeng, Zhuo; Zhou, Chengyu; Yin, Wenhui; Chen, Tao; Han, Te; Xie, Yongmin; Zhou, Aiguo (Frontiers in Physiology, 2025)
Introduction This study investigated whether stepwise load reduction training (SLRT) yields comparable or superior effects to medium load resistance training (MLRT) on one-repetition maximum (1RM) barbell back squat, thigh circumference (TC), muscle endurance (ME), counter movement jump (CMJ) performance, and acute blood lactate (BL) levels.Methods Thirty healthy, physically active males completed both the SLRT and MLRT protocols in a crossover design to assess acute blood lactate responses firstly. Then they were randomly assigned to SLRT, MLRT, or control (CON) groups using a sealed envelope method for an 8 weeks intervention. Anthropometric data were collected at baseline. Performance metrics (1RM, TC, ME, and CMJ) were measured at baseline, week 4, and post intervention. Blinding was not feasible due to the visible nature of interventions. To minimize bias, testing was conducted by staff not involved in training, with standardized warm-ups and protocols applied across groups. Training volume, frequency and assessment timing were matched between SLRT and MLRT. Participants were instructed to avoid other structured training, and adherence was monitored weekly. Results The results showed that both SLRT and MLRT significantly improved 1RM and ME, but SLRT produced greater gains. No significant differences were observed in TC. Additionally, SLRT led to significantly better CMJ performance and higher BL levels at immediate, 4th, 7th, and 9th minutes post exercise. The CON group performed significantly worse on all long-term outcomes compared to both SLRT and MLRT. While both SLRT and MLRT effectively enhance muscle strength, SLRT yields superior improvements in 1RM, ME, CMJ performance, and acute BL accumulation under equivalent training volumes.Discussion These results suggest that SLRT may offer enhanced anaerobic conditioning benefits and superior adaptation potential. However, the findings should be interpreted with consideration of certain limitations, including the homogeneity of the sample and the relatively short intervention duration.